PELATIHAN PEMBUATAN PERANGKAT CBT (Computer Based Test) UNTUK MEMPERSIAPKAN SEKOLAH SIAGA BENCANA - Dini Nurmalasari; Mardhian Fadhly; Wenda Novayanti; Yuli Fitrisia (LPPM Universitas Abdurrab, 2021)
Learning process between students and teachers includes face-to-face activities and evaluation in the form of exams. In certain conditions, such as the natural disasters of haze or disease outbreaks, the teaching and learning process cannot be done directly. One alternative to face-to-face activities in the teaching and learning process is SPADA (Online Learning System), which was inaugurated nationally in 2014. This online system allows students and teachers to be in different places but can carry out online learning. Apart from online learning, exams or evaluations can also be done online. There are many free applications that can be used to create an online exam system, known as CBT. However, not all teachers understand and know how to use and make the CBT application. In this Community Service activity, lecturers in the Computer Engineering Study Program provide training and workshops on how to use and create CBT applications online through the Zoom Cloud streaming application. The workshop which was held for two days was attended by approximately 225 participants from high school and equivalent teachers who came from various cities in Riau and a small part from outside Riau and outside Sumatra.